Tranformasi Birokrasi Menuju Good Governance: Implementasi Program SIPADI Pada Pembayaran Pajak Restoran di Badan Pendapatan Daerah - Bahri, Jesica Pratiwi; Purnamasari, Hanny (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the implementation of the Regional Tax Information System (SIPADI) in the restaurant tax payment process in Karawang Regency and its impact on taxpayer compliance. The research uses a narrative study method with a qualitative approach through in-depth interviews with several restaurant taxpayers who have used SIPADI. Karawang Regency, known as one of Indonesia’s major industrial areas, has experienced rapid growth in the number of restaurants due to the high influx of workers and economic activity. This situation highlights the urgency of effective tax regulation and monitoring systems. The findings show that although SIPADI provides convenience and improves transparency, several challenges remain, including technical issues and discrepancies between reported data and actual transactions. Therefore, a follow-up policy such as the establishment of a minimum taxable income threshold for restaurants is needed to prevent tax evasion and to increase contributions to Local Own-Source Revenue (PAD). Keywords: SIPADI, restaurant tax, narrative study, taxpayer compliance